Methodology and Mysticism: For an Integral Study of Religion - Völker, Fabian (Religions, 2022)
By means of a paradigmatic investigation of the subjective, interior side of mysticism, this article intends to contribute to the methodological debate within religious studies. By tracing the possibilities of empirical access to their limit, it will be shown that the study of religion cannot possibly do without recourse to a phenomenological mode of access of its material and without philosophical reflection on its significance if it wants to do full justice to its distinctive object of research in its most essential features. The holistic approach urged here, requires, as its constitutive basis, an integrative methodology, one that is in principle able to combine all fruitful lines of inquiry in a methodically differentiated and reflexively judicious manner and, thus, to allow each of the complementary ways of looking to have their own legitimacy respected as they unfold their specific questions. Seeking a robust support for the methodological pluralism of an integral study of religion, which will keep it from succumbing to the empiricist reductionism of the cultural studies perspective, I propose that a transcendental philosophical method should be considered as a basis. Furthermore, this empowers a critical expansion and deepening of new approaches to the phenomenology of religion and a constructive interaction with the intercultural philosophy of religion.